How many variables are sufficient for the determination disturbance of cholesterol metabolism? - Půlpán, Zdeněk (Univerzita Pardubice, 2009)
The paper describes the methodology of the so-called advanced data mining with help the programme parcel STATISTICA on the example of a "healthy-ill" ensemble.
Keywords: Data Mining; answer tree methodology; statistical modelling and decision; data management